Therapeutic Approaches in Regenerative Medicine of Cardiovascular Diseases: From Bench to Bedside - Aránega, Antonia; Bustamante, Milán; Marchal, Juan Antonio; Perán, Macarena; López, Elena; Álvarez, Pablo; Rodríguez-Serrano, Fernando; Carrillo, Esmeralda (IntechOpen, 2011)
None